PENGARUH ZIS, INFLASI, KOPERASI, DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Salwa Syarif (2023)
For two decades, Indonesia's economic growth has fluctuated. This economic growth can be influenced by various factors including ZIS (zakat infaq alms), inflation, cooperatives and unemployment. therefore this study aims to determine the effect of ZIS, inflation, cooperatives and unemployment on Indonesia's economic growth. Using quantitative methods using secondary data, time series data with saturated sampling method, namely a sampling technique where all members of the population are used as samples with time series regression analysis techniques. In this study, the sample data came from the Central Bureau of Statistics and the National Zakat Agency (Baznas). The results of this study are the cointegration test results indicating that the five variables in this study are cointegrated, which means that the five variables have a long-term relationship. The results of the Granger causality test show that ZIS, inflation, cooperatives, and unemployment have no causal relationship between variables. In the estimation of the VECM model and in the short term ZIS, inflation, cooperatives and unemployment do not have a significant effect on economic growth. In the long term ZIS, cooperatives, inflation has a significant effect while unemployment has no significant effect on economic growth.